Tycho Hedéns Väg : trafikrum blir stadsrum - Lindeqvist, Petra (SLU/Dept. of Urban and Rural Development, 2009)
Tycho Hedéns Väg in Uppsala has evolved from being a through fare passage and highway to the oversized road frame running through the city it is today. At the present time, due to the relocation of the E4 highway east of Uppsala, Tycho Hedéns road creates a barrier between the north eastern area of Uppsala and the remaining parts of the city centre. The road is designed to endure heavy traffic and high speed limits, generating a surrounding urban area were inhabitants are complied to follow the standards set for a high traffic-accessible environment. Furthermore, the heavy traffic has led to the turning of both urban roadsides away from the actual road. The aim of this project and proposal is to show the possibilities of how the innate features of Tycho Hedéns road can be used more advantageously to mend the city area of Uppsala. The space created between housing and the crossing parks, accompanied by its central location is considered to be the area of great potential for Tycho Hedéns road.